MUATAN HOTS PADA SOAL UJIAN SEMESTER GANJIL BAHASA INDONESIA DI SEKOLAH MENEGAH KEJURUAN - Kurniawan, Budi; Mukhlis, Muhammad (UIR Press, 2024)
This study aims to find out the percentage of Higher Order Thinking Skills questions in the exam questions using Bloom revsi Taxonomy contained in the odd semester exam questions Indonesian at SMKN 1 Pekanbaru with a total of 50 questions. This type of research uses qualitative research, the method used is content analysis which then the results of the research will be described. The results showed that the percentage of occurrence of lower order thinking skills tends to dominate as much as 54% with the question of the level of understanding C2 is more dominant and then followed by applying C3 and remembering C1. Meanwhile, in the category of questions that develop higher order thinking skills, the percentage obtained is relatively low at 30% almost the average form of C4 level questions, and some levels evaluate C5 but unfortunately there is no finding about the level of creating C6.